2012
DOI: 10.12968/bjon.2012.21.17.1026
|View full text |Cite
|
Sign up to set email alerts
|

Exploring advanced nursing practice: past, present and future

Abstract: This article examines the nature of advanced nursing practice. It identifies confusion around the terms of advanced nurse practitioners (ANPs), nurse practitioners and specialist nurses, and identifies what advanced practice is. The history of how ANPs evolved is discussed from its haphazard development to a more organised approach. Current advanced practice is identified, along with NHS plans for nurse development. Law, ethics and professional accountability are examined in relation to the additional responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…These needs are furthermore highlighted because the economic situation, questions with CNS education, and divergent views on the CNS role are the most significant future threats emphasized by the experts. In the current economy there is inevitable value in a policy to guide efficient APN role development; however, in many countries the absence of policies and regulation has led to insufficiently designed role introduction (Bryant‐Lukosius & DiCenso, ; Duke, ; Furlong & Smith, ; Weaver Moore & Leahy, ). Additionally, it has been noted that regulatory issues may take a long time to actualize (Arslanian‐Engoren, ; Bryant‐Lukosius et al., ); therefore, prioritizing the issues on which to focus can be informed through the Delphi process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These needs are furthermore highlighted because the economic situation, questions with CNS education, and divergent views on the CNS role are the most significant future threats emphasized by the experts. In the current economy there is inevitable value in a policy to guide efficient APN role development; however, in many countries the absence of policies and regulation has led to insufficiently designed role introduction (Bryant‐Lukosius & DiCenso, ; Duke, ; Furlong & Smith, ; Weaver Moore & Leahy, ). Additionally, it has been noted that regulatory issues may take a long time to actualize (Arslanian‐Engoren, ; Bryant‐Lukosius et al., ); therefore, prioritizing the issues on which to focus can be informed through the Delphi process.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nomenclature and generic definitions of an advanced practice nurse vary between and even within countries (Baldwin, ; Dowling, Beauchesne, Farrelly, & Murphy, ; Hutchinson, ; International Council of Nurses [ICN], ; Jokiniemi, Pietilä, Kylmä, & Haatainen, ; Lewandowski & Adamle, ; Pulcini et al., ), it is generally agreed that APN is carried out by autonomous, experienced practitioners who possess an advanced level of skills and knowledge acquired through graduate nursing education (ICN, ). An APN role is actualized through advanced nursing, specialization, and expansion of scope of practice, which underpin nurses’ activities in advanced clinical practice, practice development, education, consultation, research, and clinical leadership (Bryant‐Lukosius, DiCenso, Browne, & Pinelli, ; Dowling et al., ; Duke, ; Gardner, ; Hanson & Hamric, ; Hutchinson, ; Jokiniemi et al., ; Roche, ). Role specialization and expansion provide advanced practice nurses with their secondary title, such as clinical nurse specialist (CNS; Ruel & Motyka, ).…”
mentioning
confidence: 99%
“…The practice of CNSs operating as staff members and not attaining supernumerary status, to take on a CNS caseload needs to be addressed in order for CNSs to collaborate and lead the profession 26 . It is recognised that CNSs influence practice through nursing activities, practice development, education, consultation, research and clinical research [27][28][29][30][31][32] . Our findings are similar to Acton Shapiro 33 who highlighted that CNSs are not being utilised to their full extent and are therefore unable to have the desired impact on practice that might be anticipated [33][34] .…”
Section: While Differences May Exist Among Cns Roles/definitions Betwmentioning
confidence: 99%
“…). However, the regulation of advanced practice has stalled or is not being considered in some countries for many reasons (Institute of Medicine , Duke , Ellerbe & Regen ). The different titles and levels of education being used to designate the advanced nurse practitioner are contributing to the lack of official recognition of the role and to adversely impacting the professional role.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that outcomes from care delivered by advanced nurse practitioners have enhanced patient care in relation to level of satisfaction, quality and access (Ritz et al 2000, Green & Davis 2005, Sheer & Wong 2008, Stanley et al 2009, Gerrish et al 2011. However, the regulation of advanced practice has stalled or is not being considered in some countries for many reasons (Institute of Medicine 2011, Duke 2012, Ellerbe & Regen 2012. The different titles and levels of education being used to designate the advanced nurse practitioner are contributing to the lack of official recognition of the role and to adversely impacting the professional role.…”
Section: Discussionmentioning
confidence: 99%